2022
DOI: 10.38142/ijesss.v2i1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Accrual Reliability, Debt Level And Cash Flow Volatility On Earnings Persistence

Abstract: This research is entitled “The Effect of Accrual Reliability, Debt Level and Cash Flow Volatility on Earnings Persistence”. The research question is “Is the persistence of earnings is affected by accrual reliability, debt levels and cash flow volatility? The research objective is to examine empirically the effect of accrual reliability, debt levels and cash flow volatility on the earnings persistence. Accrual reliability, level of debt and cash flow volatility are independent variables in this study while earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…The results of this study show that Leverage (Lv) has no effect on Earning Persistence (EP). These results are supported by the research of Widiatmoko and Indarti (2019) but not supported by the research of Dayanti et al (2021). As is the case with other independent variables, the cause of Lv has no effect on EP because during the study period there was a period when the Covid-19 Pandemic occurred, which was 3 years out of the 5 years accounting period in this study.…”
Section: Effect Of Leverage On Earning Persistencecontrasting
confidence: 61%
See 1 more Smart Citation
“…The results of this study show that Leverage (Lv) has no effect on Earning Persistence (EP). These results are supported by the research of Widiatmoko and Indarti (2019) but not supported by the research of Dayanti et al (2021). As is the case with other independent variables, the cause of Lv has no effect on EP because during the study period there was a period when the Covid-19 Pandemic occurred, which was 3 years out of the 5 years accounting period in this study.…”
Section: Effect Of Leverage On Earning Persistencecontrasting
confidence: 61%
“…Nevertheless, not all studies show the influence of leverage on earnings persistence. According to the research by Dayanti et al (2021), leverage has a positive impact on profit persistence, but research by Widiatmoko and Indarti (2019) found leverage has a negative impact on profit persistence. Thus, the level of leverage becomes a factor in determining the amount of profit and predicting future earnings.…”
Section: Introductionmentioning
confidence: 99%